Comparison of the Chemical and Sensorial Evaluation of Dark Chocolate Bars - Ylenia Pieracci (MDPI AG, 2021)
As it mimics olfactory perception, headspace analysis is frequently used for examination of products like chocolate, in which aroma is a key feature. Chemical analysis by itself, however, only provides half the picture, as final consumer’s perception cannot be compared to that of a Gas Chromatography-Mass Spectrometry (GC-MS) port, but rather to a panel test assessment. The aim of the present study was the evaluation of combined chemical (by means of headspace solid-phase microextraction and GC-MS) and panel test data (by means of a sensory evaluation operated by 6 untrained panelists) obtained for 24 dark chocolate bars to assess whether these can discriminate between bars from different brands belonging to different commercial segments (hard discount, HD; supermarket, SM; organic bars, BIO). In all samples, with the only exception of one supermarket bar (in which esters exhibited the highest relative abundance), pyrazines were detected as the most abundant chemical class (HD: 56.3–74.2%; BIO: 52.0–76.4%; SM: 31.2–88.9%). Non-terpene alcohols, aldehydes, and esters followed as quantitatively relevant groups of compounds. The obtained data was then subjected to hierarchical cluster (HCA) and principal component (PCA) analysis. The statistical distribution of samples obtained for the chemical data did not match that obtained with panelists’ sensorial data. Moreover, although an overall ability of grouping samples of the same commercial origin was evidenced for hard discount and supermarket bars, no sharp grouping was possible.